Association Between Vitamin D and Influenza: Meta-Analysis and Systematic Review of Randomized Controlled Trials - Zhu, Zhixin; Zhu, Xiaoxia; Gu, Lanfang; Zhan, Yancen; Chen, Liang; Li, Xiuyang (Frontiers in Nutrition, 2022)
Background: Vitamin D supplementation improves the immune function of human body and can be a convenient way to prevent influenza. However, evidence from randomized controlled trials is inconclusive. So, this meta-analysis was preformed to systematically summarize results from Randomized Controlled Trials (RCTs) studying the protective effect of vitamin D supplementation on influenza. Methods: RCTs regarding the association between vitamin D supplementation and the risk of influenza were identified by searching PubMed, Cochrane library, Embase and Scopus from inception until present (last updated on 25 September 2021). The effects were pooled and expressed in terms of risk ratio (RR) with 95% confidence interval (95% CI). Heterogeneity was assessed using Cochran’s Q and I2. Results: 9 trials including 4762 individuals were ultimately eligible after scanning. The summarized results of the included studies indicates that substitution with vitamin D significantly reduces the risk of influenza infections (RR= 0.85, 95% CI:0.73-0.98). There was no evidence of a significant heterogeneity among studies (I2= 29%, P=0.150), Meta-regression analysis manifested that country, latitude, average age, economic level and average daily vitamin D intake were not influential factors. No evidence of publication bias was observed. Omission of any single trial had little impact on the pooled risk estimates. Conclusion: The meta-analysis produced a corroboration that vitamin D supplement has a preventive effect on influenza. The conclusions need to be validated by RCTs with better design, larger samples, and higher quality, and the influences of age, season, baseline levels of vitamin D and the type of influenza virus need to be further analyzed.